Insights into Stem Cell Factor chemotactic guidance of neural crest cells revealed by a real-time directionality-based assay - Rovasio, Roberto Americo (2012)
The extracellular environment through which neural crest cells (NCCs) translocate and differentiate plays a crucial role in the determination of cell migration and homing. In the trunk, NCC-derived melanocyte precursor cells (MPCs) take the dorsolateral pathway and colonize the skin, where they differentiate into pigment cells (PCs). Our hypothesis was that the skin, the MPCs’ target tissue, may induce a directional response of NCCs toward diffusible factor(s). We show that the treatment of in vitro NCCs with skin extract (SE) or Stem Cell Factor (SCF) contributes to maintaining proliferative activity, accelerates melanocyte differentiation, and guides a subpopulation of NCCs by chemotaxis toward the gradient source of these factors, suggesting that they may represent the MPCs’ subpopulation. Current data on stimulated directional persistence of NCCs supports the participation of diffusible molecules in the target colonization mechanism, guiding MPCs to migrate and invade the skin. Our results show similar effects of SE and SCF on NCC growth, proliferation and pigment cell differentiation. Also, the use of a proven real-time directionality-based objective assay shows the directional migration of NCCs toward SE and SCF, indicating that the epidermal SCF molecule may be involved in the chemotactic guidance mechanism of in vivo NCCs. Although SCF is the strongest candidate to account for these phenomena, the nature of other factor(s) affecting NCC-oriented migration remains to be investigated. This data amplifies the functional scope of trophic factors by involving them in new cell behaviors such as molecular guidance in the colonization mechanism of embryonic cells.